Nanatsu-no-kata, Endo-no-kata, and Joge-no-kata ―A pedagogical and qualitative biomechanical evaluation of Hirano Tokio’s kuzushi (unbalancing) concept as part of skill acquisition for throwing techniques in Kodokan judo (Revista de Artes Marciales Asiáticas, 2014)
Hirano Tokio (1922-1993) was a talented judo champion who developed his own pedagogical approach towards teaching and practicing kuzushi (unbalancing) and tsukuri (preparation), two critical skills for successfully applying judo throws. In his approach, Hirano emphasizes the use of rotational unbalancing preceded by strategic movements that mimic water waves. No biomechanical analysis of Hirano’s wave system has previously been attempted. The purpose of this paper is to provide a detailed survey of Hirano’s didactic system comparing it with traditional Kodokan teachings, and to assess its biomechanical foundations. The fluid dynamic modeling of the several kinds of waves proposed by Hirano is mathematically complicated and heavily relies on Boussinesq differential equations. Given the involvement of numerous parameters in determining the hydrodynamic behavior of water (depth, period of waves, saliency, temperatures, currents, shape of the coastal line, water density, wind) which are absent in the surroundings of a pair of two judoka moving indoors on a tatami, Hirano’s system appears limited to a mere visualization and metaphysical interpretation of judo. The lack of empirical and experimental data available obtained in large groups of students taught according to Hirano’s approach make it so far impossible to conclude whether it facilitates kuzushi and tsukuri skill acquisition. Ultimately Hirano’s wave-based kuzushi/tsukuri does not alter the biomechanical analysis previously proposed by Sacripanti, as it still is all about general action invariants aimed to close the distance between both opponents, to break the opponent’s symmetry, and to apply one of the infinite options to achieve this.